Phosphorylation and Circadian Molecular Timing - Brenna, Andrea; Albrecht, Urs (Frontiers in Physiology, 2020)
Endogenous circadian rhythms are biological processes generated by an internal body clock. They are self-sustaining, and they govern biochemical and physiological processes. However, circadian rhythms are influenced by many external stimuli to reprogram the phase in response to environmental change. Through their adaptability to environmental changes, they synchronize physiological responses to environmental challenges that occur within a sidereal day. The precision of this circadian system is assured by many posttranslational modifications (PTMs) that occur on the protein components of the circadian clock mechanism. The most ancient example of circadian rhythmicity driven by phosphorylation of clock proteins was observed in cyanobacteria. The influence of phosphorylation on the circadian system is observed through different kingdoms, from plants to humans. Here, we discuss how phosphorylation modulates the mammalian circadian clock, and we give a detailed overview of the most critical discoveries in the field.